Rational Suicide in the Elderly : Clinical, Ethical, and Sociocultural Aspects - McCue, Robert E.; Balasubramaniam, Meera (Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive view of rational suicide in the elderly, a group that has nearly twice the rate of suicide when chronically ill than any other demographic. Views of rational suicide are evolving, particularly because of a growing older population with a longer life expectancy. However, there is little guidance for geriatric mental health professionals about this. The book's frame of reference does not endorse a single point-of-view about the legitimacy of rational suicide, but serves as a resource for both those clinicians who agree that older people may rationally commit suicide and those who believe that this wish may require further assessment and treatment. The first chapters of the book address the question of whether suicide in the elderly can be rational from bio-ethical and clinical perspectives and whether the nearness of death in late-life adults means that clinicians should approach suicide differently in that group than in younger adults. Clinical criteria for rational suicide in the elderly are proposed in this book for the first time. Another chapter addresses legal issues for clinicians treating older adults who wish a rational end of life. The book examines rational suicide in the elderly through history and across cultures, while also addressing the special case of Baby Boomers. Unlike any other book, this text examines the issue from existential, spiritual, psychological, and psychodynamic perspectives. Another chapter takes a novel look at the possibility of terminal mental illness and how this relates to suicide. This book is the first to consider psychotherapeutic, spiritual, and pharmacological interventions for an older adult who is contemplating suicide without a diagnosable mental illness. The book concludes with a commentary on modern society, aging, and rational suicide that ties all of these elements together, making this the ultimate guide for addressing rational desires for suicide among the elderly. Rational Suicide in the Elderly is an excellent resource for all medical professionals with potentially suicidal patients, including geriatricians, geriatric and general psychiatrists, geriatric nurses, social workers, and public health officials.